2019
DOI: 10.1007/s10803-019-04172-0
|View full text |Cite
|
Sign up to set email alerts
|

Fast Periodic Visual Stimulation EEG Reveals Reduced Neural Sensitivity to Fearful Faces in Children with Autism

Abstract: We objectively quantified the neural sensitivity of school-aged boys with and without autism spectrum disorder (ASD) to detect briefly presented fearful expressions by combining fast periodic visual stimulation with frequency-tagging electroencephalography. Images of neutral faces were presented at 6 Hz, periodically interleaved with fearful expressions at 1.2 Hz oddball rate. While both groups equally display the face inversion effect and mainly rely on information from the mouth to detect fearful expressions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 104 publications
(150 reference statements)
4
41
0
Order By: Relevance
“…However, the response amplitudes indicate a substantially reduced emotion-specific neural sensitivity in the ASD group: In contrast to studies describing a general emotion-processing deficit in ASD, we only observed selectively lower responses to angry and fearful faces, as compared to TDs. These findings confirm and extend our previously reported results (Van der Donck et al, 2019).…”
Section: Reduced Neural Sensitivity To Expressive Faces In Asd Is Emosupporting
confidence: 94%
See 2 more Smart Citations
“…However, the response amplitudes indicate a substantially reduced emotion-specific neural sensitivity in the ASD group: In contrast to studies describing a general emotion-processing deficit in ASD, we only observed selectively lower responses to angry and fearful faces, as compared to TDs. These findings confirm and extend our previously reported results (Van der Donck et al, 2019).…”
Section: Reduced Neural Sensitivity To Expressive Faces In Asd Is Emosupporting
confidence: 94%
“…With the present study, we consolidate and extend the findings of a lower neural sensitivity in schoolaged boys with ASD to rapidly detect fearful faces, as compared to matched TDs (Van der Donck et al, 2019). Here, by applying FPVS-EEG with several facial emotions, we can broaden our understanding of the underlying neural nature of facial expression processing in ASD: Is this lower neural sensitivity emotion-specific (e.g., only for fear) or general (i.e., generalizable to multiple expressions)?…”
Section: Present Studysupporting
confidence: 77%
See 1 more Smart Citation
“…This novel tool offers great advantages in terms of objectivity in the identification and quantification of selective responses of interest in the frequency domain of the EEG spectrum, as well as high sensitivity (i.e., high signal-to-noise ratio). A pioneering study by Van der Donck et al (124,125) applied a frequency-tagging EEG oddball paradigm to assess the neural sensitivity for rapid changes in emotional expressions, revealing reduced neural discrimination responses for fearful and angry faces in children with ASD and predicting clinical status with an 87% accuracy at the individual level.…”
Section: Eeg Researchmentioning
confidence: 99%
“…To dissociate these alternatives, EEG paradigms directly contrasting neutral and emotional facial expressions are needed. A particularly promising approach for this would be the administration of a fast periodic visual stimulation oddball frequency-tagging paradigm, as has been applied in ASD (124,125). Thus far, this method has not been applied in primary psychosis, but it was recently administered in patients with velocardiofacial (22q11.2 deletion) syndrome, which is a well-known high-risk group for psychosis (147).…”
Section: Eeg Researchmentioning
confidence: 99%